Sistem Ekonomi Islam: Suatu Pendekatan Filsafat, Nilai-nilai Dasar, dan Instrumental - Abbas, Anwar (Faculty of Shariah and Law, 2012)
Islamic economic system has its own system. It is not a combination between capitalism and socialism. Islamic economic system did not put human as a central (anthroposentrism) but as a Gid servant (abid) that should serve and carry out the tasks entrusted to the servant (khalifah). Therefore, the economic practice must uphold the values of ownership, the values of justice, freedom, balance, and in accordance with the fraternity and togetherness guided by religious teachings in order to create good personal living arrangements, social, and nationalDOI: 10.15408/aiq.v4i1.2086